152k views
1 vote
Divide 9x2 – 6x + 2 by (–1 + 3x)

User Patm
by
6.2k points

2 Answers

6 votes

Explanation:

The first step is to setup the division problem


3x - 1 \sqrt{9 {x}^(2) } - 6x + 2

Next we divide


9 {x}^(2) / 3x = 3x

So now we have to multiply 3x by 3x and -1 by 3x


3x * 3x = 9 {x}^(2) \\ - 1 * 3x = - 3x

Then


\: \: \: \: 9 {x}^(2) - 9 {x}^(2) = 0


- 6x + 3x = - 3x

Now we divide


- 3x / 3x = - 1

Now multiply


- 1 * - 1 = 1

Now we


- 3x + 3x = 0 \\ 2 - 1 = 1

So the answer is

3x-1 Remains 1/3x-1


3x - 1 + \: \frac {1}{3x - 1}

User Prakash Karena
by
5.5k points
2 votes

Answer:

3 x − 1 − 1/ − 3 x + 1

Explanation:

User Kyle Lahnakoski
by
5.9k points